Antibacterial PE composite material and preparation method thereof

By adding antibacterial agent Mn-CeO2/HAP@PDA-HDTBP and other components to polyethylene (PE), the antibacterial PE composite material is prepared by melt blending method, which solves the problem of insufficient mechanical properties and antibacterial properties of PE materials, and improves the mechanical properties of the material and optimizes the antibacterial properties.

CN119859339AActive Publication Date: 2025-04-22FUZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510191642.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-04-22
Estimated Expiration
2045-02-21

AI Technical Summary

Technical Problem

In its wide application, polyethylene (PE) has problems such as general mechanical properties, good impact resistance, but low tensile strength, and poor creep resistance. In particular, its insufficient antibacterial properties have affected its application in life and industry.

Method used

The antibacterial PE composite material is prepared by adding the antibacterial agent Mn-CeO2/HAP@PDA-HDTBP to PE, combining glycerol, antioxidant and polyethylene wax, and melt blending method is used to prepare the antibacterial PE composite material to improve its mechanical properties and antibacterial properties.

Benefits of technology

The mechanical properties of antibacterial PE composite materials are improved and antibacterial performance optimization are achieved, ensuring the stability of the material and efficient antibacterial effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859339A_ABST
    Figure CN119859339A_ABST
Patent Text Reader

Abstract

The invention discloses an antibacterial PE composite material and a preparation method thereof, and belongs to the field of polymer composite materials. The antibacterial PE composite material is prepared from the following raw materials in parts by weight: 90 parts of PE, 1 to 6 parts of an antibacterial agent Mn-CeO2 / HAP (at) PDA-HDTBP, 1.5 to 2.5 parts of glycerol, 1 to 2 parts of an antioxidant 1010 and 1 to 3 parts of polyethylene wax. The antibacterial agent is prepared by taking modified hydroxyapatite as a carrier and loading manganese-doped cerium oxide, Mn-CeO2 obtained by doping CeO2 with Mn and HAP which is modified by PDA and HDTBP and simultaneously improves the antibacterial performance of the antibacterial agent and the dispersity and compatibility of the antibacterial agent in a matrix are used, so that the performance of the antibacterial agent is fully exerted in the matrix. Mn-CeO2 / HAP-PDA-HDTBP is adopted as the antibacterial agent, the antibacterial performance and mechanical performance of PE can be effectively improved, and the PE composite material with excellent performance is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer composite materials, and in particular relates to an antibacterial PE composite material and a preparation method thereof. Background Art

[0002] Polyethylene (PE) is a thermoplastic resin obtained by polymerization of ethylene, and its output accounts for about 1 / 4 of the total plastics. PE has excellent low temperature resistance (the lowest operating temperature can reach -100~-70℃), low heat resistance, which improves with the increase of relative molecular mass and crystallinity, good chemical stability, and can withstand most acid and alkali corrosion. PE is widely used in the production of films, daily necessities, various sizes of hollow containers for industrial use, pipes, calendering belts and ligatures for packaging, ropes, fishing nets and weaving fibers, wires and cables, etc. However, the mechanical properties of PE are general, with good impact resistance, low tensile strength, and poor creep resistance. Polyethylene is a linear polymer with a structure similar to that of alkanes. It belongs to a high molecular long-chain aliphatic hydrocarbon. Since the -CC- chain is a flexible chain and a linear long chain, polyethylene is a very flexible thermoplastic polymer. Because the molecule is symmetrical and there is no polar group, the intermolecular force is relatively small. The wide application of PE in life and improving its antibacterial properties are key issues concerning thousands of households.

[0003] Therefore, the development of antibacterial PE plastics has significant social and economic value. Summary of the invention

[0004] The purpose of the present invention is to provide an antibacterial PE composite material and a preparation method thereof. The present invention has a scientific and reasonable formula, a simple and practical process flow, and by adding an antibacterial agent, the produced PE composite material has excellent mechanical properties and antibacterial properties.

[0005] To achieve the above object, the present invention adopts the following technical solution: An antibacterial PE composite material comprises, by weight, 90 parts of PE, 1-6 parts of an antibacterial agent, 1.5-2.5 parts of glycerol, 1-2 parts of an antioxidant, and 1-3 parts of polyethylene wax. The antibacterial agent is Mn-CeO2 / HAP@PDA-HDTBP.

[0006] The specific preparation process of the antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP is as follows: (1) Preparation of HAP: 5.6 g of Ca(NO3)2·4H2O was added to 300 mL of anhydrous ethanol, and magnetically stirred at 60°C until uniform. Then 1.7 g of phosphorus pentoxide (P2O5) was slowly added and stirred until a sol was formed and gelled at room temperature. The formed gel was dried at 80°C for 24 hours and then calcined at 700°C for 3 hours to obtain HAP. (2) Preparation of HAP@PDA-HDTBP: 1 g HAP and 2 g dopamine hydrochloride were added to 400 mL Tris buffer (PH=8.5), and then 100 mL anhydrous ethanol was added. After ultrasonic treatment for 1 h, HAP@PDA was obtained by filtration and drying. Then 2 g of dried HAP@PDA and 1 g hexadecyl tributyl phosphonium bromide (HDTBP) were added to 200 mL ethanol aqueous solution (concentration 95%), ultrasonic treatment for 1 h, and stirring at 80 °C for 6 h. After the reaction was completed, the mixture was filtered, washed with ethanol and deionized water several times, and vacuum dried at 60 °C for 24 h to obtain HAP@PDA-HDTBP. (3) Preparation of Mn-CeO2 / HAP@PDA-HDTBP: Under continuous stirring, 125 mL of NaOH aqueous solution (1.33 mol / L) was gradually added to 125 mL of Mn(CH3COO)2·2H2O aqueous solution (0.44 mol / L), and then 1.76 g of Ce(NO3)3·6H2O and 8.9 g of HAP@PDA-HDTBP were added. The resulting suspension was then transferred to a hydrothermal reactor for hydrothermal reaction. After the reaction was completed, the mixture was cooled to room temperature, centrifuged, and the product was washed several times with deionized water and ethanol, and dried under vacuum at 60 °C for 4 h to obtain Mn-CeO2 / HAP@PDA-HDTBP.

[0007] Furthermore, in step (1), the mass ratio of phosphorus pentoxide to Ca(NO3)2·4H2O is 1:3.3.

[0008] Furthermore, in step (3), the temperature of the hydrothermal reaction is 100° C. and the time is 10 hours.

[0009] The present invention also provides a method for preparing the above antibacterial PE composite material, comprising the following steps: (1) The antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP was mixed evenly with glycerol, antioxidant 1010 and polyethylene wax, added into a high-speed mixer and mixed evenly with PE, and then dried at 60 °C for 1 h; (2) adding the dried material in step (1) into a twin-screw extruder and performing extrusion granulation to obtain a masterbatch; (3) Dry the masterbatch obtained in step (2) in a vacuum drying oven for 1 hour, and then perform injection molding to obtain an antibacterial PE composite material.

[0010] Furthermore, in step (1), the rotation speed of the high-speed stirrer is 300 r / min and the temperature is 60° C.

[0011] Furthermore, in step (2), the temperature of the first section of the twin-screw extruder is 220°C, the temperature of the second section is 215°C, the temperature of the third section is 210°C, the temperature of the fourth section is 205°C, and the temperature of the fifth section is 200°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0012] Furthermore, in step (3), an injection molding machine is used for injection molding, and the temperatures of the injection molding machine from the feed port to the discharge port are respectively: first section temperature: 250°C, second section temperature: 240°C, third section temperature: 230°C, fourth section temperature: 220°C, fifth section temperature: 210°C; injection molding pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial PE composite material.

[0013] The beneficial effects of the present invention are: (1) The cerium oxide used in the present invention is a stable metal particle with good catalytic activity and stability. Cerium ions have excellent antibacterial properties and excellent adsorption properties that can adsorb bacteria and improve antibacterial efficiency. They also have high thermal stability and chemical stability, and their structure is not easily destroyed. The variable valence characteristics of CeO2 give it excellent photoelectric properties and can be doped in other materials for modification. Cerium oxide particles, especially nano-scale cerium oxide particles, have significant antibacterial properties. Combining Mn with CeO2 particles in the form of ion doping to form Mn-CeO2 can further improve the antibacterial efficiency.

[0014] (2) Hydroxyapatite (HAP) is a component of biological bones, has good adsorption, biocompatibility and bioactivity, and can be effectively dispersed in high molecular polymer resins. The calcium ions in hydroxyapatite are relatively large, and the linking bonds in the compound are relatively weak, so they can be easily replaced with other ions. The cerium salt and manganese salt dissolved in deionized water can be exchanged with the calcium ions in hydroxyapatite by hydrothermal method, so that Mn and cerium ions are doped into hydroxyapatite, which will also add new properties of Ce and Mn.

[0015] (3) The antibacterial agent of the present invention uses non-toxic hydroxyapatite (HAP) as a carrier. The HAP modified by dopamine and hexadecyl tributylphosphonium bromide can not only be well dispersed in the polymer resin, but also has certain antibacterial properties. After being added to the polymer resin, it can improve its mechanical properties to a certain extent. Manganese-doped cerium oxide (Mn-CeO2) is loaded on the surface of HAP to obtain the antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP. Because Mn-CeO2 has excellent thermal stability, chemical stability and antibacterial properties, it can improve the overall stability of the antibacterial agent, work synergistically with HAP@PDA-HDTBP, improve the dispersibility of the antibacterial agent in the matrix resin, and further improve the antibacterial properties of the polymer matrix. At the same time, when Mn-CeO2 is loaded onto HAP@PDA-HDTBP, the occurrence of agglomeration can be effectively reduced, and the antibacterial properties of the antibacterial agent can be fully exerted. The obtained antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP will have more excellent performance. The obtained modified material is applied as an antibacterial agent to a polymer matrix to prepare an antibacterial material with excellent antibacterial properties and stable existence.

[0016] (4) The antibacterial PE composite material prepared by the present invention has a scientific and reasonable formula, a simple and practical process flow, and the antibacterial agent is prepared by melt blending. The antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP uses HAP@PDA-HDTBP with excellent biocompatibility as a carrier to load Mn-CeO2 thereon. Since HAP is difficult to modify, PDA is used to increase active sites for it and then HDTBP is used to modify it. The obtained HAP@PDA-HDTBP can be effectively dispersed in the high molecular polymer resin. Therefore, when Mn-CeO2 with good antibacterial properties is loaded on the surface of HAP@PDA-HDTBP, under the action of HAP@PDA-HDTBP, the antibacterial agent can be more evenly and effectively dispersed in the matrix resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the Fourier infrared image of the antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP prepared in the present invention.

[0018] Figure 2 This is the SEM image of the HAP prepared in Example 1.

[0019] Figure 3 This is the SEM image of Mn-CeO2 / HAP@PDA-HDTBP prepared in Example 1.

[0020] Figure 4 This is a SEM image of the antibacterial PE composite material prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with specific embodiments to make the present invention easier to understand, but the present invention is not limited to these embodiments.

[0022] Example 1 The preparation method of the antibacterial PE composite material comprises the following steps: 1. Specific preparation process of antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP: 1) Preparation of HAP: 5.6 g of Ca(NO3)2·4H2O) was added to 300 mL of anhydrous ethanol, and magnetically stirred at 60°C until uniform, and then 1.7 g of phosphorus pentoxide (P2O5) was slowly added, and stirring was continued until a sol was formed, and gelled at room temperature. The formed gel was dried at 80°C for 24 hours, and then calcined at 700°C for 3 hours to obtain HAP; 2) Preparation of HAP@PDA-HDTBP: 1g HAP and 2g dopamine hydrochloride were added to 400mL Tris buffer (PH=8.5), and then 100mL anhydrous ethanol was added. After ultrasonication for 1h, HAP@PDA was obtained by filtration and drying. Then 2g of dried HAP@PDA and 1g hexadecyl tributyl phosphonium bromide (HDTBP) were added to 200mL ethanol solution (95%), ultrasonication for 1h, and stirring at 80°C for 6h. After the reaction was completed, the mixture was filtered, washed with ethanol and deionized water several times, and vacuum dried at 60°C for 24h to obtain HAP@PDA-HDTBP. 3) Preparation of Mn-CeO2 / HAP@PDA-HDTBP: 125 mL of NaOH aqueous solution (1.33 mol / L) was gradually added to 125 mL of Mn(CH3COO)2·2H2O aqueous solution (0.44 mol / L) under continuous stirring. 1.76 g of Ce(NO3)3·6H2O and 8.9 g of HAP@PDA-HDTBP were added to the above solution, and then the resulting suspension was transferred to a hydrothermal reactor and heated at 100°C for 10 h. After cooling to room temperature, the product was washed several times with deionized water and ethanol after centrifugation, and dried under vacuum at 60°C for 4 h to obtain Mn-CeO2 / HAP@PDA-HDTBP.

[0023] 2. Add 1 part by weight of Mn-CeO2 / HAP@PDA-HDTBP to 2 parts by weight of glycerol, 1 part by weight of antioxidant 1010, and 1 part by weight of polyethylene wax, mix evenly, and then mix evenly with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, and then place in a 60°C oven to dry for 1 hour.

[0024] 3. Add the dried raw materials into a twin-screw extruder, the temperature of the first section of the twin-screw extruder is 220°C, the temperature of the second section is 215°C, the temperature of the third section is 210°C, the temperature of the fourth section is 205°C, and the temperature of the fifth section is 200°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0025] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 250°C, second section temperature: 240°C, third section temperature: 230°C, fourth section temperature: 220°C, fifth section temperature: 210°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial PE composite material.

[0026] Figure 1 This is the Fourier transform infrared image of the antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP prepared by the present invention. The infrared spectrum is at 570 cm -1 and 607 cm -1 The absorption peak at 1035-1096 cm -1 The peaks at 1633 cm -1 and 3572 cm -1 The peak at 1598 cm is the hydrogen-oxygen stretching vibration peak in hydroxyapatite. -1 A weak characteristic peak appeared at 2930 cm-1, which corresponds to the C=C stretching vibration absorption peak in the aromatic ring of PDA, indicating that HAP was modified by PDA. -1 The characteristic peak of -CH3 was found at , which is the characteristic group of HDTBP. This shows that HAP@PDA-HDTBP was successfully prepared, and then it was combined with Mn-CeO2 as a carrier to obtain the antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP.

[0027] Figure 2 This is a SEM image of the HAP prepared in Example 1. As can be seen from the image, the surface of the prepared HAP is relatively smooth.

[0028] Figure 3This is the SEM image of Mn-CeO2 / HAP@PDA-HDTBP prepared in Example 1. It can be seen from the figure that the antibacterial agent Mn-CeO2 is loaded on the surface of the modified HAP with larger and rough particles, which proves that the composite antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP is successfully prepared.

[0029] Example 2 The preparation method of the antibacterial PE composite material comprises the following steps: 1. The specific preparation process of the antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP is the same as that in Example 1; 2. Add 2 parts by weight of Mn-CeO2 / HAP@PDA-HDTBP to 2 parts by weight of glycerol, 1 part by weight of antioxidant 1010, and 1 part by weight of polyethylene wax and mix evenly, then mix evenly with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, and then place in a 60°C oven to dry for 1 hour.

[0030] 3. Add the dried raw materials into a twin-screw extruder, the temperature of the first section of the twin-screw extruder is 220°C, the temperature of the second section is 215°C, the temperature of the third section is 210°C, the temperature of the fourth section is 205°C, and the temperature of the fifth section is 200°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0031] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 250°C, second section temperature: 240°C, third section temperature: 230°C, fourth section temperature: 220°C, fifth section temperature: 210°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial PE composite material.

[0032] Example 3 The preparation method of the antibacterial PE composite material comprises the following steps: 1. The specific preparation process of the antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP is the same as that in Example 1; 2. Add 3 parts by weight of Mn-CeO2 / HAP@PDA-HDTBP to 2 parts by weight of glycerol, 1 part by weight of antioxidant 1010, and 1 part by weight of polyethylene wax and mix evenly, then mix evenly with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, and then place in a 60°C oven to dry for 1 hour.

[0033] 3. Add the dried raw materials into a twin-screw extruder, the temperature of the first section of the twin-screw extruder is 220°C, the temperature of the second section is 215°C, the temperature of the third section is 210°C, the temperature of the fourth section is 205°C, and the temperature of the fifth section is 200°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0034] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 250°C, second section temperature: 240°C, third section temperature: 230°C, fourth section temperature: 220°C, fifth section temperature: 210°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial PE composite material.

[0035] Example 4 The preparation method of the antibacterial PE composite material comprises the following steps: The preparation method of the antibacterial PE composite material comprises the following steps: 1. The specific preparation process of the antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP is the same as that in Example 1; 2. Add 4 parts by weight of Mn-CeO2 / HAP@PDA-HDTBP to 2 parts by weight of glycerol, 1 part by weight of antioxidant 1010, and 1 part by weight of polyethylene wax and mix evenly, then mix evenly with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, and then place in a 60°C oven to dry for 1 hour.

[0036] 3. Add the dried raw materials into a twin-screw extruder, the temperature of the first section of the twin-screw extruder is 220°C, the temperature of the second section is 215°C, the temperature of the third section is 210°C, the temperature of the fourth section is 205°C, and the temperature of the fifth section is 200°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0037] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 250°C, second section temperature: 240°C, third section temperature: 230°C, fourth section temperature: 220°C, fifth section temperature: 210°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial PE composite material.

[0038] Example 5 The preparation method of the antibacterial PE composite material comprises the following steps: 1. The specific preparation process of the antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP is the same as that in Example 1; 2. Add 5 parts by weight of Mn-CeO2 / HAP@PDA-HDTBP to 2 parts by weight of glycerol, 1 part by weight of antioxidant 1010, and 1 part by weight of polyethylene wax and mix evenly, then mix evenly with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, and then place in a 60°C oven to dry for 1 hour.

[0039] 3. Add the dried raw materials into a twin-screw extruder, the temperature of the first section of the twin-screw extruder is 220°C, the temperature of the second section is 215°C, the temperature of the third section is 210°C, the temperature of the fourth section is 205°C, and the temperature of the fifth section is 200°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0040] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 250°C, second section temperature: 240°C, third section temperature: 230°C, fourth section temperature: 220°C, fifth section temperature: 210°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial PE composite material.

[0041] Figure 4 This is a SEM image of the antibacterial PE composite material prepared in Example 5 of the present invention. The image clearly shows that the antibacterial filler has good compatibility with the polyethylene matrix and the dispersion of the filler in PE is also good.

[0042] Example 6 The preparation method of the antibacterial PE composite material comprises the following steps: 1. The specific preparation process of the antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP is the same as that in Example 1; 2. Add 6 parts by weight of Mn-CeO2 / HAP@PDA-HDTBP to 2 parts by weight of glycerol, 1 part by weight of antioxidant 1010, and 1 part by weight of polyethylene wax and mix evenly, then mix evenly with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, and then place in a 60°C oven to dry for 1 hour.

[0043] 3. Add the dried raw materials into a twin-screw extruder, the temperature of the first section of the twin-screw extruder is 220°C, the temperature of the second section is 215°C, the temperature of the third section is 210°C, the temperature of the fourth section is 205°C, and the temperature of the fifth section is 200°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0044] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 250°C, second section temperature: 240°C, third section temperature: 230°C, fourth section temperature: 220°C, fifth section temperature: 210°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial PE composite material.

[0045] Comparative Example 1 1. Preparation of HAP: 5.6 g of Ca(NO3)2·4H2O was added to 300 mL of anhydrous ethanol, and magnetically stirred at 60°C until uniform, and then 1.7 g of phosphorus pentoxide (P2O5) was slowly added, and stirring was continued until a sol was formed, and gelled at room temperature. The formed gel was dried at 80°C for 24 hours, and then calcined at 700°C for 3 hours to obtain HAP.

[0046] 2. Preparation of HAP@PDA-HDTBP: 1g HAP and 2g dopamine hydrochloride were added to 400mL Tris buffer (PH=8.5), and then 100mL anhydrous ethanol was added. After ultrasonication for 1h, HAP@PDA was obtained by filtration and drying. Then 2g dried HAP@PDA and 1g hexadecyl tributyl phosphonium bromide (HDTBP) were added to 200mL ethanol solution (95%), ultrasonication for 1h, and stirring at 80°C for 6h. After the reaction was completed, the mixture was filtered, washed with ethanol and deionized water several times, and vacuum dried at 60°C for 24h to obtain HAP@PDA-HDTBP.

[0047] 3. Add 5 parts by weight of HAP@PDA-HDTBP to 2 parts by weight of glycerol, 1 part by weight of antioxidant 1010, and 1 part by weight of polyethylene wax and mix evenly, then mix evenly with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, and then place in a 60°C oven to dry for 1 hour.

[0048] 4. Add the dried raw materials into a twin-screw extruder, the temperature of the first section of the twin-screw extruder is 220°C, the temperature of the second section is 215°C, the temperature of the third section is 210°C, the temperature of the fourth section is 205°C, and the temperature of the fifth section is 200°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0049] 5. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 250°C, second section temperature: 240°C, third section temperature: 230°C, fourth section temperature: 220°C, fifth section temperature: 210°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial PE composite material.

[0050] Comparative Example 2 1. Preparation of Mn-CeO2: Under continuous stirring, 125 mL of NaOH aqueous solution (1.33 mol / L) was gradually added to 125 mL of Mn(CH3COO)2·2H2O aqueous solution (0.44 mol / L). 1.76 g of Ce(NO3)3·6H2O was added to the above solution, and then the resulting suspension was transferred to a hydrothermal reactor and heated at 100°C for 10 hours. After the reaction was completed, it was cooled to room temperature, centrifuged, and the product was washed several times with deionized water and ethanol, and vacuum dried at 60°C for 4 hours to obtain Mn-CeO2.

[0051] 2. Add 5 parts by weight of Mn-CeO2 to 2 parts by weight of glycerol, 1 part by weight of antioxidant 1010 and 1 part by weight of polyethylene wax and mix evenly. Then mix evenly with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C. Then place in a 60°C oven and dry for 1 hour.

[0052] 3. Add the dried raw materials into a twin-screw extruder, the temperature of the first section of the twin-screw extruder is 220°C, the temperature of the second section is 215°C, the temperature of the third section is 210°C, the temperature of the fourth section is 205°C, and the temperature of the fifth section is 200°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0053] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 250°C, second section temperature: 240°C, third section temperature: 230°C, fourth section temperature: 220°C, fifth section temperature: 210°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial PE composite material.

[0054] Comparative Example 3 1. Preparation of HAP@PDA-HDTBP: 1) Add 5.6 g of Ca(NO3)2·4H2O to 300 mL of anhydrous ethanol, stir magnetically at 60°C until uniform, then slowly add 1.7 g of phosphorus pentoxide (P2O5), continue stirring until a sol is formed, and keep gelling at room temperature. The formed gel is dried at 80°C for 24 hours and then calcined at 700°C for 3 hours to obtain HAP.

[0055] 2) 1g HAP and 2g dopamine hydrochloride were added to 400mL Tris buffer (PH=8.5), and then 100mL anhydrous ethanol was added. After ultrasonic treatment for 1h, HAP@PDA was obtained by filtration and drying. Then 2g of dried HAP@PDA and 1g hexadecyltributylphosphonium bromide (HDTBP) were added to 200mL ethanol solution (95%), ultrasonic treatment for 1h, and stirred at 80°C for 6h. After the reaction was completed, the mixture was filtered, washed with ethanol and deionized water several times, and vacuum dried at 60°C for 24h to obtain HAP@PDA-HDTBP.

[0056] 2. Preparation of Mn-CeO2: Under continuous stirring, 125 mL of NaOH aqueous solution (1.33 mol / L) was gradually added to 125 mL of Mn(CH3COO)2·2H2O aqueous solution (0.44 mol / L). In the above solution, 1.76 g of Ce(NO3)3·6H2O was added, and then the suspension was transferred to a hydrothermal reactor and heated at 100°C for 10 hours. After cooling to room temperature, the product was washed several times with deionized water and ethanol, centrifuged and vacuum dried at 60°C for 4 hours to obtain Mn-CeO2.

[0057] 3. Add 4 parts by weight of HAP@PDA-HDTBP and 1 part by weight of Mn-CeO2 to 2 parts by weight of glycerol, 1 part by weight of antioxidant 1010, and 1 part by weight of polyethylene wax, mix evenly, and then mix evenly with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, and then place in a 60°C oven to dry for 1 hour.

[0058] 4. Add the dried raw materials into a twin-screw extruder, the temperature of the first section of the twin-screw extruder is 220°C, the temperature of the second section is 215°C, the temperature of the third section is 210°C, the temperature of the fourth section is 205°C, and the temperature of the fifth section is 200°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0059] 5. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour, and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 250°C, second section temperature: 240°C, third section temperature: 230°C, fourth section temperature: 220°C, fifth section temperature: 210°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial PE composite material.

[0060] The materials obtained in the examples and comparative examples were subjected to performance tests, and the results are shown in Table 1.

[0061] Table 1 Performance test results Table 1 shows the performance test results of each embodiment and each comparative example. It can be clearly seen from the above performance test results that in Examples 1-6, as the amount of antibacterial agent added increases, the tensile strength of the PE composite material shows a trend of first increasing and then slightly decreasing, and the antibacterial performance also shows a trend of first increasing and then slightly decreasing. When the amount of antibacterial agent added reaches 6 parts, the mechanical properties decrease more. It may be that the antibacterial agent agglomerates in the matrix material, resulting in a decrease in mechanical properties. From the perspective of comprehensive performance, the effect is best when the amount of antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP added is 5 parts by weight (Example 5). It can be seen from the comparison between Comparative Example 2 and Example 5 that the compatibility of Mn-CeO2 with the matrix is ​​general, and the effect of the composite antibacterial agent is better than that of Mn-CeO2. It can be seen from the comparison between Comparative Example 1 and Example 5 that HAP@PDA-HDTBP has good compatibility with the matrix and can improve the mechanical properties of the composite material. From the comparison between Comparative Examples 1 and 2 and Example 5, it can be seen that Example 5 uses Mn-CeO2 / HAP@PDA-HDTBP as an antibacterial agent, and HAP@PDA-HDTBP can improve the compatibility of Mn-CeO2 with the matrix to a certain extent, so that the mechanical properties and antibacterial properties of the PE composite material are better than those of Comparative Examples 1 and 2.

[0062] Those skilled in the art will easily understand that the above description is only a preferred example of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An antibacterial PE composite material, characterized in that: In terms of weight, the antibacterial PE composite material includes 90 parts of PE, 1-6 parts of antibacterial agent, 1.5-2.5 parts of glycerol, 1-2 parts of antioxidant 1010, and 1-3 parts of polyethylene wax; the antibacterial agent is Mn-CeO2 / HAP@PDA-HDTBP.

2. The antibacterial PE composite material according to claim 1, characterized in that: The preparation method of the antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP comprises the following steps: (1) Preparation of hydroxyapatite: Ca(NO3)2·4H2O was added to anhydrous ethanol and magnetically stirred at 60°C until uniform. Then phosphorus pentoxide was slowly added and stirred until a sol was formed. The sol was gelled at room temperature. The formed gel was dried at 80°C for 24 hours and then calcined at 700°C for 3 hours to obtain HAP. (2) Preparation of HAP@PDA-HDTBP: 1 g HAP and 2 g dopamine hydrochloride were added to 400 mL Tris buffer, and then 100 mL anhydrous ethanol was added. After ultrasonic treatment for 1 h, the mixture was filtered and dried to obtain HAP@PDA. Then 2 g HAP@PDA and 1 g hexadecyltributylphosphonium bromide were added to 200 mL 95% ethanol aqueous solution, and ultrasonic treatment was performed for 1 h. The mixture was stirred at 80 °C for 6 h. After the reaction was completed, the mixture was filtered, washed with ethanol and deionized water, and vacuum dried at 60 °C for 24 h to obtain HAP@PDA-HDTBP. (3) Preparation of Mn-CeO2 / HAP@PDA-HDTBP: Under continuous stirring, 125 mL of 1.33 mol / L NaOH aqueous solution was gradually added to 125 mL of 0.44 mol / L manganese acetate aqueous solution, and then 1.76 g of Ce(NO3)3·6H2O and 8.9 g of HAP@PDA-HDTBP were added. Finally, the resulting suspension was transferred to a hydrothermal reactor for hydrothermal reaction. After the reaction was completed and cooled to room temperature, the product was centrifuged and washed several times with deionized water and ethanol, and vacuum dried at 60°C for 4 h to obtain Mn-CeO2 / HAP@PDA-HDTBP.

3. The antibacterial PE composite material according to claim 2, characterized in that: In step (1), the mass ratio of phosphorus pentoxide to Ca(NO3)2·4H2O is 1:3.

3.

4. The antibacterial PE composite material according to claim 2, characterized in that: The temperature of the hydrothermal reaction in step (3) is 100° C. and the time is 10 hours.

5. A method for preparing the antibacterial PE composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) The antibacterial agent Mn-CeO2 / HAP@PDA-HDTBP was mixed evenly with glycerol, antioxidant 1010 and polyethylene wax, added into a high-speed mixer and mixed evenly with PE, and then dried at 60 °C for 1 h; (2) adding the dried material in step (1) into a twin-screw extruder and performing extrusion granulation to obtain a masterbatch; (3) Drying the masterbatch obtained in step (2) in a vacuum drying oven, and then performing injection molding to obtain an antibacterial PE composite material.

6. The preparation method according to claim 5, characterized in that: The speed of the high-speed stirrer in step (1) is 300 r / min and the temperature is 60°C.

7. The preparation method according to claim 5, characterized in that: The extrusion temperatures of the twin-screw extruder in step (2) are: 220°C in the first section, 215°C in the second section, 210°C in the third section, 205°C in the fourth section, and 200°C in the fifth section; the screw speed is 10 r / min.

8. The preparation method according to claim 4, characterized in that: The drying temperature in step (3) is 60°C and the drying time is 1 hour. During injection molding, the injection temperatures from the feed port to the discharge port are: first section temperature: 250°C, second section temperature: 240°C, third section temperature: 230°C, fourth section temperature: 220°C, fifth section temperature: 210°C, injection pressure is 135 MPa, and holding pressure is 40 MPa.

Citation Information

Patent Citations

  • Antimicrobial macromolecule material and method for preparing the same

    CN101492572A

  • High-toughness antibacterial PE composite material and preparation method thereof

    CN115651299A

  • Antibacterial polyolefin composition

    JP1992077538A

  • Plastic composition including hydroxyapatite with improved antimicrobial

    KR1020170123424A